PENERAPAN MODEL DISCOVERY LEARNING DALAM PENINGKATAN KETERAMPILAN MENULIS TEGAK BERSAMBUNG PESERTA DIDIK KELAS II SEKOLAH DASAR - Sriwahyuni, Neli; Rahardjo, Rudhi; Saniyah, Saniyah; Indradni, Neny (STKIP Setiabudhi, 2021)
This study aims to apply higher order thinking skill (HOTS)-oriented learning using the Discovery Learning Model in an effort to improve cursive writing skills in grade II elementary school students. This research was carried out in several stages: KD Mapping, Competency Target Analysis, Formulation of Competency Achievement Indicators, Planning Learning Activities in accordance with the Discovery Learning Learning Model, Preparation of Learning Tools. The subject of this research is the second grade elementary school students. The result is that the application of the Discovery Learning model can improve the cursive writing skills of the second grade elementary school students. Keywords: Discovery Learning, cursive writing skills Abstrak Penelitian ini Bertujuan untuk menerapkan pembelajaran berorientasi higher order thinking skill (HOTS) menggunakan Model Discovery Learning dalam upaya meningkatkan keterampilan menulis tegak bersambung pada peserta didik kelas II Sekolah Dasar. Penelitian ini dilaksanakan dalam beberapa tahap: Pemetaan KD, Analisis Target Kompetensi , Perumusan Indikator Pencapaian Kompetensi, Merencanakan Kegiatan Pembelajaran sesuai dengan Model Pembelajaran Discovery Learning, Penyusunan Perangkat Pembelajaran. Subjek pebelitian ini adalah peserta didik kelas II Sekolah Dasar. Hasilnya bahwa Penerapan model Discovery Learning Dapat meningkatkan keterampilan menulis tegak bersambung peserta didik kelas II Sekolah Dasar. Kata Kunci: Discovery Learning, Keterampilan menulis tegak bersambung